Attention allocation and online knowledge sharing within organizations - HAAS, Martine (Institutional Knowledge at Singapore Management University, 2014)
Why do individuals allocate attention to specific problems in organizations? Viewing attention allocation as a matching process between knowledge providers and problems, we examine knowledge sharing in the context of an online discussion forum where knowledge providers respond to problems posted by other organization members. We argue that a knowledge provider is less likely to allocate attention to a problem to the extent that the problem creates cognitive load or the situation creates cognitive crowding for the provider, but that these concerns can be mitigated by expertise complementarity between the provider and the problem. Analyzing 1,251 realized matches and 12,510 unrealized matches among knowledge providers and problems posted in an online discussion forum within a global engineering firm over a 32-month period, we find evidence to support our central claim that attention allocation is driven by the features of a particular provider-problem match. The implications for organizational theories of knowledge sharing and managerial attention are discussed.